Supervisor Communication, Career Development, and Job Satisfaction as Predictors of Palm Oil Employee Performance - Muhammad Fernanda Rizaldy; Meiske Claudia; Hastin Umi Anisah; Wimby Wandary (LPPM STIE KRAKATAU, 2026)
This study investigates whether supervisor communication and career development shape employee performance at PT XYZ directly and through job satisfaction. This study responds to the scarcity of evidence concerning routine supervisor-employee interactions and organizational career support in palm oil plantation and processing operations. The study employed an explanatory quantitative design and estimated the proposed relationships using partial least squares structural equation Modelling (PLS-SEM). Responses from 67 employees were obtained through a structured five-point Likert questionnaire and processed using SmartPLS 4. Supervisor communication predicted employee performance (β =0.309) and job satisfaction (β =0.511), whereas career development predicted employee performance (β =0.232) and job satisfaction (β =0.430). Job satisfaction was associated with employee performance (β =0.455) and carried the effects of supervisor communication (β =0.232) and career development (β =0.195) on performance. The model accounted for 57.7% of the variance in job satisfaction and 70.2% in employee performance. Better supervisory communication and stronger career development practices are linked to higher performance through both direct pathways and employee satisfaction. The findings clarify the mediating function of job satisfaction in the palm oil plantation and processing context. PT XYZ should prioritize precise supervisory feedback, understandable work communication, and transparent career development procedures.